2022
DOI: 10.1039/d1cp04446j
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-stabilized hexafluorides of first-row transition metals

Abstract: Fluorine chemistry was demonstrated to show the importance of stretching the limits of chemical synthesis, oxidation state, and chemical bonding at ambient conditions. Thus far, the highest fluorine stoichiometry of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…However, their high‐pressure XRD experiment demonstrated that FeF 3 tends to form an amorphous phase above 42 GPa, with no further changes up to 62 GPa [23] . Recent theoretical work suggested no phase transition in FeF 3 until 237 GPa [17] . Moreover, Lin et al .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, their high‐pressure XRD experiment demonstrated that FeF 3 tends to form an amorphous phase above 42 GPa, with no further changes up to 62 GPa [23] . Recent theoretical work suggested no phase transition in FeF 3 until 237 GPa [17] . Moreover, Lin et al .…”
Section: Introductionmentioning
confidence: 97%
“…[23] Recent theoretical work suggested no phase transition in FeF 3 until 237 GPa. [17] Moreover, Lin et al reported a denser tetragonal structure of FeF 3 at pressures of 78-130 GPa and temperatures up to 1,900 K. [24] Notably, none of these studies have identified any FeÀ F compound featuring a structure with an iron coordination number exceeding 6. While the smaller radius of F anion compared to O anion suggests a higher likelihood of Fe forming hypercoordination with F, the existence of 8-coordinated Fe in FeÀ F compounds remains unconfirmed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In simple ionic compounds, Fe typically coordinates with 4 or 6 anions, such as carbon, [10] pnictogens, [11] chalcogens, [12] and halogens, [13] with notable exceptions being Fe 7 O 10 and Fe 2 O 3 , [12a] which exhibit mixed coordination, [14] and 8‐coordinated δ ‐Fe 3 O 4 [15] under high pressures. Numerous theoretical studies have proposed 8‐coordinated Fe in two‐dimensional FeB 6 and other highly compressed Fe‐bearing solids, such as FeCl@300 GPa, [16] FeF 4 @116 GPa, [17] FeF 6 @274 GPa, [17] FeN 4 @250 GPa, [18] and FeOOHe@120 GPa, [19] among others. However, these configurations have not been experimentally confirmed, likely due to the challenges in preparing unconventional stoichiometric compounds and the technical limitations at ultra‐high pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has revealed that the post-TM element Au and the 3d middle elements, Cr, Mn, and Fe, have high oxidation states (Z+6) at high pressures. [25][26][27] Calculating the valence orbital energies of atoms (VOEA) allows the construction of a curve of the VOEA for all TM elements. This curve reveals that most of the d orbital energy levels are much higher than that of the F 2p orbital (Fig.…”
Section: Introductionmentioning
confidence: 99%